2010
DOI: 10.2527/jas.2009-2332
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Feeding behavior of goats1,2

Abstract: Factors influencing the feeding behavior of goats include grazing management practices, type of vegetation and season, breed and stage of production, group size, and properties of diets fed in confinement. Considerable information has been gathered from visual observation during daylight. However, tools are now available to characterize the feeding behavior of goats while grazing and while in confinement throughout the day. Global positioning system collars can be used to assess horizontal and vertical distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 65 publications
(90 reference statements)
0
45
0
2
Order By: Relevance
“…Goats are selective feeders and their food intake can be reduced under confinement; therefore, careful attention should be observed when determining ad libitum intake (Goetsch et al 2010). Fedele et al (2002) observed that the DM intake of free choice goats increased by 12% compared to those under control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Goats are selective feeders and their food intake can be reduced under confinement; therefore, careful attention should be observed when determining ad libitum intake (Goetsch et al 2010). Fedele et al (2002) observed that the DM intake of free choice goats increased by 12% compared to those under control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to Epps (2002), cattle are animals of twilight habit; that is, they are more active at nightfall and at dawn, which are the times when they present their peaks of feeding. Like sheep and goat, cattle can also adequate their feeding behavior according to type, availability, and chemical characteristics of the feed in order to meet their needs (Goetsch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number of goats has steadily increased over recent years (Borchardt et al 2010). Goats pose a major threat to the sensitive ecosystem due to their characteristic feeding habits (Goetsch et al 2010). However, as goats are officially banned from the investigated pastures (State Forest Agency of the Kyrgyz Republic 1996), it is difficult to obtain reliable information on their amount.…”
Section: Study Areamentioning
confidence: 99%
“…Schmidt, M. 2005, Schmidt, K. 2007. In particular, the rising numbers of goats, which strongly harm the shrub and tree layer, and prevent natural regeneration (Fernandez-Lugo et al 2009, Goetsch et al 2010, is an object of great concern.…”
Section: Actual Situation Of the Kyrgyz Montane Pasturesmentioning
confidence: 99%